DATA PROTECTION BY MODIFICATION HARD DISK SYSTEM PARTITIONS - Павлов, В. (Science-based technologies, 2010)
There have been considered the methods of information security on electronic media. There have been shown the advantages of the «winchester’s» system partition encryption over the encryption of specified files, folders and volumes. There have been demonstrated the ways to make information security stronger due to the change of the Master Boot Record content, in particular, Partition Table.